The Influence Of Corporate Social Responsibility, Green Accounting, Environmental Perfomance, Green Innovation, and Carbon Emissions Disclosure On Financial Perfomance - Putri Dwi Shinta Nuriyah; Dendi Purnama; Arief Nurhandika (Islamic Accounting Journal, 2025)